Knowledge, attitudes, and practices of pharmacists on hierarchical management of COPD: a cross-sectional study in Jiangsu Province - Wu, Qiuhui; Meng, Yanhong; Zhang, Ruobin; Ding, Yuhang; Wang, Yongsheng; Zhang, Jinping (Frontiers in Medicine, 2025)
PurposeThis study assessed pharmacists’ knowledge, attitudes, and practices regarding hierarchical management of COPD patients, examining influencing factors to inform standardization.Patients and methodsA cross-sectional survey was conducted from December 2022 to March 2023 using convenience sampling, yielding 206 valid responses via WeChat-distributed questionnaires. Data analysis employed t-tests, ANOVA, and multiple linear regression.ResultsPharmacists’ mean scores were: knowledge (6.13 ± 1.96), attitudes (27.56 ± 3.37), and practices (21.02 ± 6.06). Regression analysis highlighted correlations between knowledge scores and gender, education, and hospital level (p < 0.05); attitudes and academic qualifications (p < 0.05); practices and hospital level (p < 0.05).ConclusionPharmacists demonstrated moderate knowledge, positive attitudes, and average practices in COPD management. Tailored training programs addressing educational and institutional disparities are essential to enhance their capacity in hierarchical COPD care.